Didactic conditions of formations of pedagogical culture of the future music teachers (Pedagogy of Higher and Secondary Education, 2013)
Sidorenko T. D. Didactic conditions of formations of pedagogical culture of the future music teachers.In the article the feasibility of organizing a particular activity for its efficiency and the need for certain conditions for the implementation of teaching a particular set of processes designed to – the formation of a highly qualified professional.
Keywords: teaching conditions; pedagogical culture; music culture; music and aesthetic education; the learning process